Free radicals in human health and disease - Rani, Vibha; Yadav, Umesh Chand Singh (Springer India Imprint: Springer, 2015)
The role of oxidative stress in human disease has become an area of intense interest. Free radicals, a normal product of metabolism, exist in all aerobic cells in balance with biochemical antioxidants. Environmental stress increases the levels of free radicals drastically, thereby disturbing the equilibrium between free radical production and the antioxidant capability causing oxidative stress. Over the years, ROS has been implicated in the pathologies of various diseases like cancer, neurological disorder, cardiovascular diseases rheumatoid arthritis, diabetes etc. This book provides an in depth critical state-of-art reviews from established investigators on free radicals, ROS associated pathogenesis of human diseases, biomarkers of oxidative damage, antioxidants, phytonutrients and other related health concerns of modern society. The present book is aimed at graduate students, researchers in academia, industry, and clinicians with the interest in redox biology. Special attention has been devoted to the topic of ROS signalling, oxidative stress induced human pathologies & antioxidative therapies. The book consists of four parts in specified topics based on the current literatures for the better understanding of the readers with respect to their subject-wise interests. The first section of the book provides an overview about the ROS production and their measuring tools and techniques followed by the mechanisms involved in the oxidative stress in the second section. The third section describes the involvement of oxidative stress in different human diseases and the last section focuses on the different strategies to ameliorate oxidative stress induced stress.